Relationship between acoustic emission signal strength and damage evaluation of reinforced concrete structure: Case studies - Md Nor, Noorsuhada
Relationship between acoustic emission (AE) signal strength and damage evaluation has been reviewed. Several case studies have been referred to get information on that relationship. The notion or any opinion relates to the case study also had been discussed. Reviews of AE signal strength relate to damage evaluation of reinforced concrete structure and other materials are significantly useful for newly researchers.